ОИЛАДА МУСИҚА ЁРДАМИДА БОЛАДА ЭСТЕТИК ТАРБИЯНИ ШАКЛЛАНТИРИШ МЕТОДЛАРИ - Сеит-Энон, Амиде Юсуф қизи (SCIENCE and SOCIETY, 2023)
The article discusses the means of developing children’s talent through musical and aesthetic education in the family. The methods of forming the aesthetic education of the child with the help of music in the family are shown.